Kemampuan Menyimak dengan Teknik Menjawab Pertanyaan pada Siswa Kelas XI SMK Katolik Kefamenanu - Sofia Nea (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
This research aims at identifying scrutinize comprehension by using interview technique to the students at second grade SMK Katolik Kefamenanu Timor Tengah Utara regency in academic year 2017/2018. Method used in this research is qualitative descriptive. Subject in this research were students at second grade of SMK Katolik Kefamenanu, while the object in this research was news scrutinize by interview technique. Theory used in this research is scrutinizs theory that could determine correctness and incorrectness of students assignment. Data analysis toward students comprehension in scrutinizing of news text shows that thet students get total score in interval 75 – 100 where fourteen students was in very good category, five students was in good category, while a students was in enough category.